2016
DOI: 10.1136/bjsports-2015-095437
|View full text |Cite
|
Sign up to set email alerts
|

Injection therapies for plantar fasciopathy (‘plantar fasciitis’): a systematic review and network meta-analysis of 22 randomised controlled trials

Abstract: CRD42015017353.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 75 publications
0
33
1
Order By: Relevance
“…As the current NMA is the first to examine the comparative effectiveness of the most common treatments for PHP, it is difficult to directly compare the findings of the present study with those of previous NMAs which examined a limited number of treatments,58 or compared dosage/technique for specific treatment options 59. Previous reviews collectively indicate that exercise and foot orthoses are promising interventions for short-term and medium-term improvements in pain and function 60 61.…”
Section: Discussionmentioning
confidence: 92%
“…As the current NMA is the first to examine the comparative effectiveness of the most common treatments for PHP, it is difficult to directly compare the findings of the present study with those of previous NMAs which examined a limited number of treatments,58 or compared dosage/technique for specific treatment options 59. Previous reviews collectively indicate that exercise and foot orthoses are promising interventions for short-term and medium-term improvements in pain and function 60 61.…”
Section: Discussionmentioning
confidence: 92%
“…Albeit reported the short-term positive effect of this treatment 31 , it is also well documented that corticosteroid injections are correlated to the risk of the plantar fascia rupture 31,59 . However, a recent review and meta-analysis study has not showed this major adverse effect 29 .…”
Section: Details Of the Included Articlesmentioning
confidence: 99%
“…Autologous whole blood, botulinum toxin, dehydrated amniotic membrane injections were also considered [28][29][30] . Surgical intervention is performed when PF symptoms persist after different and repetitive conservative treatments.…”
Section: Blood Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They include networks that compare exercise versus drug treatments for mortality in various conditions,22 different physical activity and other interventions for osteoarthritis,23 24 and different interventions for knee arthroplasty25 lateral elbow tendinopathy and epicondylalgia26 27 and plantar fasciitis 28. Network meta-analyses are still susceptible to reporting biases and the other biases that traditional pairwise meta-analyses may suffer from.…”
Section: Prospective Meta-analysismentioning
confidence: 99%